A laminated composite material and its preparation method and use
Through the laminated composite process of laminated composite materials, the problems of complex composite processes, high cost and difficult reprocessing in the prior art are solved, and the multi-performance improvement of electronic product shell materials is achieved and the production efficiency of electronic product shell materials is improved.
Patent Information
- Application Number
- CN202211225476.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-09
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-10-09
AI Technical Summary
The composite materials of existing electronic products shells are complex and costly, and it is difficult to process after the composite is completed, and the defective rate is high. The design, manufacturing and modification costs of equipment production lines are also very high.
Laminated composite materials are used, and the film layer, plastic layer and metal layer are laminated and composited through structural bonding film to form a brand new composite sheet. This process simplifies the process flow, improves processing efficiency, and reduces production costs through the lamination and composite process of the adhesive film.
It realizes the surface properties of electronic product shell materials such as scratch resistance, easy decoration, skin-friendly, and good feel, as well as internal properties such as impact resistance, heat conductivity, light weight, and bendability. It has a simple process and high processing efficiency, reducing production costs.
Smart Images

Figure BDA0003879597610000091 
Figure HDA0003879597620000011 
Figure HDA0003879597620000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic product shells, and in particular to a laminated composite material and a preparation method and application thereof. Background Art
[0002] In addition to display touch screens, the appearance shell material is a very important appearance component of electronic products. At present, the appearance shell materials used in electronic consumer products including mobile phones, tablets, watches and bracelets, laptops, smart speakers, wearable devices (including various headphones, glasses and other AR / VR hardware, etc.) are generally metal (advantages of good thermal conductivity / disadvantages of being too heavy), plastic (advantages of low cost / disadvantages of low strength), glass (advantages of beautiful appearance / disadvantages of fragility), ceramics (advantages of good texture / disadvantages of high cost), etc. Each of these materials has its advantages and disadvantages. The disadvantage of plastic shells is that the hardness is not high enough and the texture is not good. It is easy to give consumers a cheap feeling. The biggest disadvantage of metal material is that it is heavy, and the disadvantage of glass is that it is fragility. The disadvantage of ceramics is that the yield rate is very low, so the cost is very high. It is not suitable for large-scale use and promotion, so some electronic product shells will use composite materials.
[0003] Existing composite materials for electronic products have complex composite processes and high costs. After composite materials are completed, reprocessing is difficult and requires one-time molding according to product design. The defective rate is high, and the cost of designing, manufacturing and modifying equipment production lines is very high. Summary of the invention
[0004] In view of the above-mentioned shortcomings of the prior art, an object of the present invention is to provide a laminated composite material and a preparation method and use thereof, so as to solve the problems in the prior art.
[0005] To achieve the above-mentioned purpose and other related purposes, the present invention is obtained through the following technical solutions.
[0006] The present invention provides a laminated composite material, which comprises a film layer, a first adhesive film layer, a plastic layer, a second adhesive film layer and a metal layer in sequence from one side to the other side; the film layer and the plastic layer are fixedly connected by the first adhesive film layer; the plastic layer and the metal layer are fixedly connected by the second adhesive film layer.
[0007] According to the above technical solution of the present application, the material of the film layer is selected from any one or more of polyimide (abbreviated as PI), polypropylene (abbreviated as PP), nylon (abbreviated as PA), polyester (abbreviated as PET), low-density polyethylene (abbreviated as LDPE), polyvinyl alcohol (abbreviated as PVA), polyvinyl chloride (abbreviated as PVC) and polystyrene (abbreviated as PS).
[0008] According to the above technical solution of the present application, the polypropylene includes CPP and BOPP.
[0009] According to the above technical solution of the present application, the material of the plastic layer is selected from any one or more of PET, PC, ABS, PP and PVC.
[0010] According to the above technical solution of the present application, the material of the metal layer is selected from stainless steel and / or aluminum. Preferably, the material of the metal layer is pre-treated stainless steel and / or pre-treated aluminum.
[0011] During the pretreatment, an intermediate layer or other microstructure is formed on the metal surface to improve the adhesion of the adhesive film to the metal surface in the laminated composite material.
[0012] After pretreatment, an intermediate layer is formed on the surface of the metal layer, and the thickness of the intermediate layer is 0.001-10 μm.
[0013] According to the technical solution described above, the preprocessing includes the following steps:
[0014] 1) Flatten the metal layer by a metal flattening machine;
[0015] 2) Clean and dry;
[0016] 3) Chemical treatment and drying.
[0017] Preferably, the chemical treatment is carried out by coating, spraying or soaking with chemical agents, and the chemical agents include any one or more of silane coupling agents, phosphating agents, silanizing agents or passivating agents. The chemical groups of the chemical agents form strong chemical bonds at the bonding interface, which can ultimately greatly improve the adhesion of the metal material surface to the adhesive film.
[0018] According to the technical solution described above, the first adhesive film layer and the second adhesive film layer can be melted at 50-70° C. to achieve primary bonding, and undergo chemical crosslinking reaction and solidify at 50-200° C.
[0019] According to the technical solution described above, the material of the first adhesive film layer and the second adhesive film layer is selected from any one or more of polyurethane adhesive film, EVA hot melt adhesive, epoxy adhesive and acrylic pressure sensitive adhesive.
[0020] According to the technical solution described above, the thickness of the thin film layer is 5 to 200 μm.
[0021] According to the technical solution described above, the thickness of the plastic layer is 5 to 200 μm.
[0022] According to the technical solution described above, the thickness of the metal layer is 5 to 200 μm.
[0023] According to the technical solution described above, the thickness of the first adhesive film layer is 10-100 μm.
[0024] According to the technical solution described above, the thickness of the second adhesive film layer is 10-100 μm.
[0025] The present invention also discloses a method for preparing the laminated composite material as described above, comprising:
[0026] 1) pre-attaching the first adhesive film layer on the surface of the film layer and pressing it together; pre-attaching the second adhesive film layer on the surface of the metal layer and pressing it together;
[0027] 2) pre-laminating on two surfaces of the plastic layer and pressing them together;
[0028] 3) curing the first adhesive film layer and the second adhesive film layer;
[0029] Alternatively, the steps include:
[0030] a) pre-bonding the first adhesive film layer on one side of the plastic layer, and pre-bonding the second adhesive film layer on the other side of the plastic layer;
[0031] b) The film layer and the metal layer are then laminated, pressed and cured.
[0032] According to the preparation method described above, before the first adhesive film layer is pre-attached to the surface of the thin film layer, a pattern is printed and colored on the inner side of the thin film layer according to the design.
[0033] According to the preparation method described above, the pressing pressure is greater than 15N per square centimeter.
[0034] According to the preparation method described above, the pre-lamination further includes a process of removing bubbles from the laminating surface.
[0035] According to the preparation method described above, the curing can be completed by temperature, pressure, electron beam or ultraviolet light using corresponding curing equipment according to the material system of the first adhesive film layer and the second adhesive film layer.
[0036] According to the preparation method described above, after curing and forming, the plate is cut or bent according to actual needs.
[0037] The invention also discloses the use of the laminated composite material as described above for electronic product housings.
[0038] In view of the shortcomings of the prior art, the present invention provides a laminated composite material for electronic product housings and a preparation method thereof, by using a structural adhesive film to laminate and compound different types of materials to form a new composite board. The new composite board formed by compounding different materials has excellent surface properties (scratch resistance, easy decoration, skin-friendly, good hand feel, etc.) and good internal properties (impact resistance, heat conduction, light weight, bendable to a certain extent, etc.), and has high processing efficiency and simple process.
[0039] The technical solution of the present invention has the following technical effects:
[0040] 1. The laminated composite material proposed in the present invention is a three-layer composite of a film layer, a plastic layer and a metal layer. The use of the appearance film ensures that the appearance parts are scratch-resistant and easy to decorate. The use of the middle layer of plastic can ensure impact resistance and the passage of electromagnetic signals. The use of the lower metal layer can provide support for the overall structural strength, thereby improving the performance, appearance and strength of the appearance parts of electronic consumer products.
[0041] 2. The manufacturing process of the laminated composite material of the present invention can directly perform three-layer composite lamination through two layers of adhesive film by using the lamination composite process of adhesive film. The process is simple and can improve the processing efficiency. The process uses the viscosity of the adhesive film itself for positioning and pre-lamination. When defects occur, the film can be torn off for pre-lamination, which greatly improves the processing yield and reduces the production cost.
[0042] 3. The laminated composite material of the present invention can still retain a certain reprocessing capacity after the plastic layer, the metal layer and the plastic layer are thinned, and can be used as a semi-finished product after production. There is no need to design a production line separately according to the terminal product, which reduces the cost of designing, manufacturing and modifying the production line. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Shown is a schematic structural diagram of the laminated composite material of the present invention.
[0044] Figure 1 Component number description
[0045] 1 Thin film layer
[0046] 2 Plastic layers
[0047] 3 Metal Layer
[0048] 4. First film layer
[0049] 5 Second film layer
[0050] Figure 2 It is a schematic diagram showing the testing method of the adhesion strength in the present invention.
[0051] 6 is the sample to be tested, and 7 is the cured polyurethane film layer
[0052] Figure 3 Schematic diagram of acceptable tearing state.
[0053] Figure 4 This is a tearing state diagram of the laminated composite material obtained by combining the metal plate in Example 1 with Example 5.
[0054] Figure 5 This is a tearing state diagram of the laminated composite material obtained by combining the metal plate in Example 2 with Example 5.
[0055] Figure 6 This is a tearing state diagram of the laminated composite material obtained by combining the metal plate in Example 3 with Example 5.
[0056] Figure 7 This is a tearing state diagram of the laminated composite material obtained by combining the metal plate in Example 4 with Example 5.
[0057] Figure 8 This is a tearing state diagram of the laminated composite material obtained by combining the metal plate in Comparative Example 1 with Example 5. DETAILED DESCRIPTION
[0058] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0059] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0060] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between the steps explicitly mentioned, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. The change or adjustment of their relative relationship shall also be regarded as the scope of the present invention without substantially changing the technical content.
[0061] like Figure 1As shown, an embodiment of the present invention provides a specific laminated composite material, which includes a thin film layer 1, a first adhesive film layer 4, a plastic layer 2, a second adhesive film layer 5 and a metal layer 3 in sequence from one side to the other; the thin film layer 1 is fixedly connected to the plastic layer 2 through the first adhesive film layer 4; the plastic layer 2 is fixedly connected to the metal layer 3 through the second adhesive film layer 5.
[0062] In a specific embodiment, the material of the film layer is selected from any one or more of polyimide (abbreviated as PI), polypropylene (abbreviated as PP), nylon (abbreviated as PA), polyester (abbreviated as PET), low-density polyethylene (abbreviated as LDPE), polyvinyl alcohol (abbreviated as PVA), polyvinyl chloride (abbreviated as PVC) and polystyrene (abbreviated as PS).
[0063] In a specific embodiment, the polypropylene includes CPP and BOPP.
[0064] In a specific embodiment, the material of the plastic layer is selected from any one or more of PET, PC, ABS, PP and PVC.
[0065] In a specific embodiment, the material of the metal layer is selected from stainless steel and / or aluminum. Preferably, the material of the metal layer is pre-treated stainless steel and / or pre-treated aluminum.
[0066] During the pretreatment, an intermediate layer or other microstructure is formed on the metal surface to improve the adhesion of the adhesive film to the metal surface in the laminated composite material.
[0067] After pretreatment, an intermediate layer is formed on the surface of the metal layer, and the thickness of the intermediate layer is 0.001-10 μm, such as 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm.
[0068] According to the technical solution described above, the preprocessing includes the following steps:
[0069] 1) Flatten the metal layer by a metal flattening machine;
[0070] 2) Clean and dry;
[0071] 3) Chemical treatment and drying.
[0072] In a specific embodiment, the chemical treatment is to coat, spray or soak with a chemical agent, and the chemical agent includes any one or more of a silane coupling agent, a phosphating agent, a silanizing agent or a passivating agent. Through the chemical groups of the chemical agent, a strong chemical bond is formed at the bonding interface, which can ultimately greatly improve the adhesion of the metal material surface to the film. Specifically, the molecular structure of the silane coupling agent contained in the coating is generally YR-Si(OR)3, where Y is an organic functional group and SiOR is a silaneoxy group. Silaneoxy is reactive to inorganic substances, and organic functional groups are reactive or compatible to organic substances. Therefore, when the silane coupling agent is between the inorganic and organic interfaces, a bonding layer of an organic matrix-silane coupling agent-inorganic matrix can be formed. Specifically, silane contains two different chemical functional groups. One end can react with the hydroxyl groups on the surface of inorganic materials (such as glass fiber, silicate, metal and its oxide) to form a covalent bond; the other end can form a covalent bond with the resin, thereby combining the two materials with very different properties and improving the performance of the composite material. The silanization process can be described as a four-step reaction model: (1) the three Si-OR groups connected to silicon are hydrolyzed into Si-OH; (2) Si-OH groups dehydrate and condense to form Si-OH-containing oligosiloxanes; (3) Si-OH in the oligomer forms hydrogen bonds with OH on the surface of the substrate; (4) During the heating and curing process, the dehydration reaction is accompanied by a covalent bond with the substrate, but at the interface, only one of the silanol groups of the silane is bonded to the surface of the substrate, and the remaining two Si-OH groups are either condensed with Si-OH in other silanes or in a free state.
[0073] In a more preferred embodiment, the silane coupling agent is Henkel 8521. More preferably, the silane coupling agent is coated on the surface of the metal plate, and the coating amount is preferably the thinnest that can cover the base color.
[0074] In a more preferred embodiment, the phosphating agent is Henkel 858CF. More preferably, the metal plate is soaked in a 5-20 wt % Henkel 858CF aqueous solution for 20-60 min and then dried.
[0075] In a more preferred embodiment, the silanization agent is Bolaiful silane treatment agent. More preferably, the metal plate is soaked in an aqueous solution of Bolaiful silane treatment agent with a concentration of 5 to 20 wt% for 20 to 60 minutes, and then dried. In a more preferred embodiment, the passivation agent is Kemite Gardolene D. More preferably, the metal plate is soaked in an aqueous solution of Kemite Gardolene D with a concentration of 5 to 20 wt% for 20 to 60 minutes, and then dried.
[0076] In a preferred embodiment, the first adhesive film layer and the second adhesive film layer can melt at 50-70°C to form a primary bond, and chemically crosslink and solidify at 50-200°C. When in use, pre-lamination is a preliminary bond in a molten state. For example, the temperature of the primary bond can be 50°C, 53°C, 55°C, 58°C, 60°C, 63°C, 65°C, 68°C or 70°C. For another example, the temperature of the chemical crosslinking reaction is 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C or 200°C.
[0077] In a specific embodiment, the material of the first adhesive film layer and the second adhesive film layer is selected from any one or more of polyurethane hot melt adhesive film, EVA hot melt adhesive film, epoxy adhesive and acrylic pressure sensitive adhesive.
[0078] In a more preferred embodiment, the polyurethane hot melt adhesive film is PCF-1118 produced by Shanghai Shuanghao.
[0079] In a more preferred embodiment, the EVA hot melt adhesive film is SH-7118 produced by Shanghai Shuanghao.
[0080] In a more preferred embodiment, the epoxy adhesive is YEF-209 produced by Shanghai Yongguan.
[0081] In a more preferred embodiment, the acrylic pressure-sensitive adhesive is YAF-205 produced by Shanghai Yongguan.
[0082] In a specific embodiment, the thickness of the film layer is 5 to 200 μm, such as 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm.
[0083] In a specific embodiment, the thickness of the plastic layer is 5 to 200 μm, such as 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm.
[0084] In a specific embodiment, the thickness of the metal layer is 5 to 200 μm, such as 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm.
[0085] In a specific embodiment, the thickness of the first adhesive film layer is 10-100 μm, such as 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm.
[0086] In a specific embodiment, the thickness of the second adhesive film layer is 10-100 μm, such as 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm.
[0087] The present invention further specifically discloses a method for preparing the laminated composite material as described above, comprising:
[0088] 1) pre-attaching the first adhesive film layer on the surface of the film layer and pressing it together; pre-attaching the second adhesive film layer on the surface of the metal layer and pressing it together;
[0089] 2) pre-laminating on two surfaces of the plastic layer and pressing them together;
[0090] 3) curing the first adhesive film layer and the second adhesive film layer;
[0091] Alternatively, the steps include:
[0092] a) pre-bonding the first adhesive film layer on one side of the plastic layer, and pre-bonding the second adhesive film layer on the other side of the plastic layer;
[0093] b) The film layer and the metal layer are then laminated, pressed and cured.
[0094] In a specific embodiment, before the first adhesive film layer is pre-attached to the surface of the thin film layer, a pattern is printed and colored on the inner side of the thin film layer according to the design.
[0095] In a specific embodiment, the pressing pressure is greater than 15N per square centimeter, such as 15N, 18N, 20N, 23N, 25N, 28N or 30N.
[0096] In a specific embodiment, the pre-lamination further includes a process of removing bubbles from the laminating surface.
[0097] In a specific embodiment, the curing can be performed by using temperature, pressure, electron beam or ultraviolet light according to the material system of the first adhesive film layer and the second adhesive film layer using corresponding curing equipment.
[0098] In a specific implementation, after curing and forming, the plate is cut or bent according to actual needs.
[0099] In view of the shortcomings of the prior art, the present invention provides a laminated composite material for electronic product housings and a preparation method thereof, by using a structural adhesive film to laminate and compound different types of materials to form a new composite board. The new composite board formed by compounding different materials has excellent surface properties (scratch resistance, easy decoration, skin-friendly, good hand feel, etc.) and good internal properties (impact resistance, heat conduction, light weight, bendable to a certain extent, etc.), and has high processing efficiency and simple process.
[0100] In the embodiment of the present application, the metal flattening machine used is the Hebei Bozhan metal leveling machine; the metal layer is an aluminum alloy, and the specific aluminum alloy model is 7118; the adhesive film is a polyurethane adhesive film of Shuanghao PCF-1118; the silane coupling agent is Henkel 8521; the phosphating agent is Henkel 858CF; the silanizing agent is Bolaiful silane treatment agent; and the passivating agent is Kemit Gardolene D.
[0101] Example 1
[0102] This embodiment provides a specific method for pretreating a metal layer used for laminating composite materials, the steps are:
[0103] S1. Use a metal flattening machine to process the internal stress of the metal sheet and flatten the metal sheet;
[0104] S2. The treated surface of the metal plate is sprayed and cleaned by a high-pressure spray device to remove stains, and then the surface of the metal plate is dried and heated;
[0105] S3. After the surface of the metal plate is dried, a coating device is used to coat the treated surface of the metal plate with a silane coupling agent. A stirring device and a temperature control device may be provided on the inner wall of the tank of the silane coupling agent to prevent the silane coupling agent from precipitating. The silane coupling agent is Henkel 8521, which is a black product, and the coating amount should be the thinnest that can cover the base color.
[0106] S4. After the chemical agent coating treatment is completed, it is dried by natural evaporation for 3-5 minutes, and an intermediate layer is formed after drying.
[0107] In this embodiment, the thickness of the metal plate is 25 μm, and then the metal plate can be bonded to the adhesive film through the intermediate layer. In this embodiment, the metal layer material is treated with a chemical agent to form a coating, so as to avoid the situation where the surface can only form a weak dispersion force but lacks orientation force and induction force. Through the two chemical groups of the coating, a strong chemical bond is formed at the bonding interface, which can ultimately greatly improve the bonding force of the metal material surface to the adhesive film.
[0108] Example 2
[0109] This embodiment provides another specific method for pretreating a metal layer used for laminating a composite material, the steps being:
[0110] S1. Process the internal stress of the metal sheet through the metal flattening machine and flatten the metal sheet;
[0111] S2. The treated surface of the metal plate is sprayed and cleaned by a high-pressure spray device to remove stains, and then the surface of the metal plate is dried and heated;
[0112] S3. After the surface of the metal plate is dried, the treated surface of the metal plate is treated with Henkel 858CF phosphating agent using a device; the treated surface is immersed in a phosphating solution having a concentration of 10wt% for 30 minutes and then naturally evaporated and dried, the phosphating solution being an aqueous solution containing 10wt% Henkel 858CF phosphating agent;
[0113] S4. After the chemical spraying treatment is completed, the residual heat evaporates and dries naturally for 3-5 minutes, and an intermediate layer is formed after drying.
[0114] Example 3
[0115] This embodiment is another method for pretreating a metal layer of a laminated composite material, and the steps are:
[0116] S1. Use a metal flattening machine to treat the internal stress of the metal plate, flatten the metal plate, spray clean the surface to be treated, remove stains, and dry and heat the surface of the metal plate;
[0117] S2. After the surface of the metal plate is dried, the treated surface of the metal plate is treated with a silanization agent using a device. The silanization agent is a Bolaiful silane treatment agent. The silanization agent is immersed in an aqueous solution of a 10wt% silanization agent for 30 minutes and then dried.
[0118] S3. After the silanization agent treatment is completed, the residual heat is naturally evaporated and dried for 3-5 minutes, and an intermediate layer is formed after drying.
[0119] The thickness of the middle layer is 25μm, and then it can be bonded to the adhesive film through the middle layer. Through the two chemical groups of the coating, a strong chemical bond is formed at the bonding interface, which can ultimately greatly improve the adhesion of the metal material surface to the adhesive film and simplify the process to a certain extent.
[0120] Example 4
[0121] This embodiment is another method for pretreating a metal layer of a laminated composite material, and the steps are:
[0122] S1. Use a metal flattening machine to treat the internal stress of the metal plate, flatten the metal plate, spray clean the surface to be treated, remove stains, and dry and heat the surface of the metal plate;
[0123] S2. After the surface of the metal plate is dried, the treated surface of the metal plate is treated with a passivation agent using a spraying device. The passivation agent is specifically Kemite Gardolene D. The metal plate is immersed in an aqueous solution of a passivation agent having a concentration of 10 wt% for 30 min and then dried.
[0124] S3. After the passivation agent treatment is completed, the residual heat is naturally evaporated and dried for 3-5 minutes, and an intermediate layer is formed after drying.
[0125] The thickness of the middle layer is 25μm, and then it can be bonded to the adhesive film through the middle layer. Through the two chemical groups of the coating, a strong chemical bond is formed at the bonding interface, which can ultimately greatly improve the adhesion of the metal material surface to the adhesive film and simplify the process to a certain extent.
[0126] In any one of Examples 1 to 4, the middle layer is a plastic layer, the material of which is PET, and the film layer is a second film layer, which is a polyurethane film, specifically Shuanghao PCF-1118.
[0127] Adhesion strength test method Figure 2 As shown, Figure 2In the middle: 6 is two cross-shaped stacked samples to be tested, which are 100mm long*25mm wide*5mm thick; 7 is two polyurethane films with a thickness of 50μm, which are used to bond the edges of the two samples to be tested, and the specific distance between the edges is 6mm. The polyurethane film is formed between the two layers of the samples to be tested by hot pressing at 100℃, and the pressing pressure is 20N per square centimeter.
[0128] Before the test, the two layers of the polyurethane bonded samples were placed in an environment with a temperature of 20℃~25℃ and a relative humidity of >50% for 2 hours, and the bonding tensile strength was tested using an electronic universal testing machine at a tensile rate of 10mm / min. During the test, the maximum force required for bonding failure was recorded.
[0129] The adhesion strength test results are shown in the following table.
[0130]
[0131] Example 5
[0132] This embodiment provides a specific laminated composite material for electronic product housings. In this embodiment, the metal layer is formed by using the metal plate pretreated as in Embodiments 1 to 4, the first adhesive film layer is a polyurethane adhesive film, the second adhesive film layer is a polyurethane adhesive film, the material of the plastic layer is PET, and the material of the film layer is PI. The polyurethane adhesive film used is Shuanghao PCF-1118.
[0133] The specific process steps are:
[0134] S1. Print and color the pattern on the inner side of the film layer according to the design;
[0135] S2. After removing the release paper on the upper layer of the first film layer, the upper layer of the first film layer is positioned and pre-laminated to laminate the film layer;
[0136] The lower layer of release paper of the second adhesive film layer is removed, so that the second adhesive film layer is positioned and pre-laminated on the metal layer for lamination;
[0137] S3. After the first film layer and the second film layer are positioned and pre-laminated, bubble detection and film tearing and laminating are performed to remove bubbles;
[0138] S4. After the bubbles are removed, the lower release paper of the first film layer and the upper release paper of the second film layer are removed, and the upper and lower surfaces of the plastic layer are positioned and pre-laminated to be pressed, and the bubble detection and film tearing and re-lamination are performed to remove the bubbles;
[0139] S5. According to the material system of the first adhesive film layer and the second adhesive film layer, curing is performed by hot pressing; the temperature is 80 to 120° C., specifically 100° C.
[0140] The pressing pressure is 20N per square centimeter.
[0141] After forming, the sheet is cut or bent according to actual needs.
[0142] The laminated composite material obtained in Example 4 was tested for its surface property of scratch resistance and its internal property of impact resistance.
[0143] Scratch resistance test
[0144] 1) Visually inspect the surface to be tested to ensure there are no scratches, nicks, bubbles, cracks, peeling, scratches, etc.
[0145] 2) Take a MITSU-BISHI UNI hardness H test pencil and use a special mechanical pencil sharpener to only sharpen away the wood, leaving a complete, undamaged cylindrical pencil lead of about 5 to 6 mm;
[0146] 3) Grind the pencil lead head on 400-grit sandpaper at 90° vertically to make a smooth surface with no debris or notches on the edge. Repeat this step every time before using the pencil.
[0147] 4) Place the sample to be tested on a horizontal, stable surface, insert the sharpened pencil into the test instrument, the smooth surface of the pencil will contact the surface of the test leather, and form an angle of 45° with the horizontal plane;
[0148] 5) When the tip of the pencil just touches the surface, immediately move the pencil about 20 mm away from the operator with a pressure of 350 gf, and repeat steps 3) to 5) for a total of 3 tests;
[0149] 6) After the test is completed, use a soft cloth to gently wipe off the pencil lead debris on the surface of the sample (without damaging the rolled state of the leather surface) and check the surface to be tested.
[0150] According to the above test method, the film layer surface is not allowed to be seriously rolled up, scratched, etc.; and after testing, the scratch resistance grade of the laminated composite material formed by the metal plates obtained in Examples 1 to 4 is: Film Grade 3.
[0151] Note: For the scratches that have been determined, leave limit samples (different colors, horizontal and vertical directions) for the film.
[0152] Note: Scratch resistance level and corresponding description:
[0153] Grade 4 Very light scratches: A pencil scratch can be seen upon close observation, and there is no unevenness to the touch.
[0154] Grade 3 Slight scratches: There are sparse shallow pits on the leather surface, which will not affect the user's general use. The scratches can be slightly felt by touching with fingers, but there is no obvious curling of the leather surface.
[0155] Grade 2: Visible scratches: The leather surface is shallow and densely dotted, which is easy for users to feel. When the finger slides over it, it feels uneven and the leather surface can be felt to be curled.
[0156] Grade 1 Severe Scratches: The leather surface has fine dot-like curling, which is very easy for users to feel. When sliding fingers over the leather surface, there is a clear linear curling feeling, and the degree of curling is obvious.
[0157] Grade 0: The epidermis is scraped into pieces.
[0158] Impact resistance test
[0159] 1) Check the appearance of the shell structure to see if there is any structural defect;
[0160] 2) Place the sample test position at the center of the drop point of the drop weight tester, with the sample appearance facing upwards;
[0161] 3) Select the drop weight and drop height according to the shell material, and gently fix the shell with your hands or auxiliary objects (you can use your hands to gently support or double-sided tape to stick it);
[0162] 4) Start the equipment and test each of the four corners of the rear housing;
[0163] 5) Check the shell after the test. PC material: hammer weight 500±1g, height 40cm
[0164] Appendix: Drop weight rubber dimensions: diameter: 42±1mm; thickness: 9±1mm; edge radius: 2±0.5mm; rubber hardness: Shore hardness.
[0165] After the above impact resistance test, no fracture or brittle crack is allowed, but tearing state (caused by plastic tensile deformation) is acceptable;
[0166] Acceptable tearing conditions are as follows: Figure 3 As shown by Figure 3 It can be seen that after the scratch resistance test, there are sparse shallow pits on the leather surface, which do not affect the general use of users. The scratch position can be slightly felt by touching with fingers, but there is no obvious curling of the leather surface. The judgment factor is whether the test result exceeds the normal toughness level of the material; the paint on the surface hit by the falling hammer breaks into pieces, and a full set of coating tests are required for comprehensive judgment, and the coating test results shall prevail.
[0167] The tearing states of the laminated composite materials obtained by combining the metal plates in Examples 1 to 4 with Example 5 are as follows: Figures 4 to 7 As shown, the surface flatness is good and the impact resistance is good.
[0168] Comparative Example 1
[0169] Only the metal layer obtained by the flattening and cleaning process in Example 1 was used without chemical treatment. The impact resistance of the laminated composite material formed in Example 5 is as follows: Figure 8 shown.
[0170] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A laminated composite material, characterized in that: The laminated composite material comprises, from one side to the other side, a film layer, a first film layer, a plastic layer, a second film layer and a metal layer; the film layer and the plastic layer are fixedly connected via the first film layer; the plastic layer and the metal layer are fixedly connected via the second film layer; the material of the film layer is selected from polyimide; the material of the plastic layer is selected from PET; the first film layer and the second film layer are made of Shuanghao PCF-1118; the material of the metal layer is pretreated stainless steel or pretreated aluminum, and the pretreatment comprises the following steps: 1) Flatten the metal layer by a metal flattening machine; 2) Clean and dry; 3) chemical treatment and drying; the chemical treatment is soaking with chemical agents; the chemical agents include silanization agents or passivation agents; the silanization agent is Bolaiful silane treatment agent; The passivation agent is Gardolene D.
2. The laminated composite material according to claim 1, characterized in that: The first adhesive film layer and the second adhesive film layer can be melted at 50-70° C. to achieve primary bonding, and undergo chemical crosslinking reaction and solidification at 50-200° C.
3. The laminated composite material according to claim 1, characterized in that: The thickness of the film layer is 5 to 200 μm; And / or, the thickness of the plastic layer is 5 to 200 μm; And / or, the thickness of the metal layer is 5 to 200 μm; And / or, the thickness of the first adhesive film layer is 10 to 100 μm; And / or, the thickness of the second adhesive film layer is 10-100 μm.
4. A method for preparing a laminated composite material according to any one of claims 1 to 3, comprising: 1) pre-attaching the first adhesive film layer on the surface of the film layer and pressing it; Pre-attaching the second adhesive film layer on the surface of the metal layer and pressing it; 2) pre-laminating on two surfaces of the plastic layer and pressing them together; 3) curing the first adhesive film layer and the second adhesive film layer; Alternatively, the steps include: a) pre-bonding the first adhesive film layer on one side of the plastic layer, and pre-bonding the second adhesive film layer on the other side of the plastic layer; b) The film layer and the metal layer are then laminated, pressed and cured.
5. Use of the laminated composite material according to any one of claims 1 to 3 in electronic product housings.
Citation Information
Patent Citations
Housing and manufacturing method thereof
CN101340786A
Metal-plastic composite material and method for producing same
CN114829132A
Novel metal composite film
CN213618840U